Breaking planar liquid crystal anchoring to form controllable twist disclination loops. (24th March 2017) - Angelo, Joseph; Culbreath, Christopher; Yokoyama, Hiroshi
ABSTRACT: We have developed a new device called the dynamic cell, whereby the twist angle and cell thickness of a liquid crystal cell can be dynamically varied. For a twist angle larger than 90°, there occurs a breaking of anchoring at a certain threshold cell thickness. This structural transition converts the super-twisted state to a normal twisted state by flipping the surface director by 180°. A disclination loop separates the normal twisted region from the super-twisted region. By controlling the twist and thickness, we can stabilize this loop and calculate its line tension.